The Influence of Effectiveness and Efficiency on the Preparation of Digitalization-Based Financial Reports - Rachmawati, Ria; Maulana, Wahyu; Efendi, Junaidi (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2025)
The use of digital-based financial reports has been widely used by business actors in Pamekasan Regency. Various trainings on preparing digital-based financial reports have also been provided by the Cooperatives, SMEs and Manpower Office of Pamekasan Regency to its fostered employees. Although it has been implemented, not all parties can implement it optimally due to several factors that become obstacles. The preparation of financial reports is an urgent problem besides other problems. The purpose of this study is to find the effect of effectiveness and efficiency on the preparation of digital-based financial reports. The method used in this study is quantitative descriptive which is measured using the SPSS statistical analysis tool. The population in this study was 490 active cooperatives and a sample of 57 cooperatives. The sampling technique used purposive sampling technique. The results of the study showed that there was a positive and significant influence both partially and simultaneously between the variables of effectiveness and efficiency on the preparation of digital-based financial reports with the most dominant influence being the efficiency variable. These results are evidence that training in digitalizing financial reports needs to be redesigned by emphasizing the efficiency aspect of system use and the digital system used should be selected based on its ability to simplify processes and save resources.